The Effect of Company Size and Current Ratio on Capital Structure with Return on Asset as an Intervening Variable in Pharmaceutical Companies Listed on the IDX - Ardian, Noni; Sari, Maya Macia; Sianturi, Desvi Cristiani (PT. Publikasiku Academic Solution, 2025)
The pharmaceutical industry in Indonesia has experienced significant growth, with capital structure decisions playing a crucial role in optimizing financial performance and maximizing company value. This study aims to analyze the impact of company size and current ratio on capital structure, with return on assets (ROA) acting as an intervening variable, for pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2024. Using a quantitative approach, the research samples 6 companies selected through purposive sampling. Secondary data was obtained from annual financial statements accessed via IDX and company websites. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that company size significantly affects return on assets (ROA), which in turn influences capital structure. The current ratio also has a significant effect on both ROA and capital structure. Furthermore, company size impacts capital structure through ROA as an intervening variable. The study highlights the significant influence of both company size and current ratio on capital structure in pharmaceutical companies, providing valuable insights for financial decision-making in the industry.